Criminal Procedure — Fourth Amendment — Sixth Circuit Holds that "Pinging" a Target's Cell Phone to Obtain GPS Data Is Not a Search Subject to the Warrant Requirement. — United States v. Skinner, 690 F.3d 772 (6th Cir. 2012), reh'g and reh'g en banc denied, No. 09-6497 (6th Cir. Sept. 26, 2012) (Harvard law review, 2013)
Recently, in US v. Skinner, the Sixth Circuit held that using the global positioning system (GPS) capabilities of a target's cell phone to track his location did not constitute a Fourth Amendment search, hinging the decision on the lack of a reasonable expectation of privacy under the Katz test. By not engaging with the actual process by which police "ping" cell phones for GPS data, however, the Sixth Circuit missed a chance to decide the case more narrowly. Before trial, Skinner sought to suppress the evidence and statements that grew out of the search sparked by the pinging of the phone. Judge Phillips of the Eastern District of Tennessee adopted the recommendation of Magistrate Judge Guyton, who began his analysis by stating that cell-site data is simply data sent from a cellular phone tower to the cellular provider's computers. Because neither party argued or briefed the issue of whether a search actually occured, the court assumed that a search had taken place.